Percepções de integrantes da Comunidade Educativa sobre a liderança de um diretor de pastoral de uma instituição de ensino privada da região metropolitana de Lima - Montalván Zúñiga , Pablo Fernando (2022)
This research presents the leadership analysis of a pastoral principal of an educational institution in Metropolitan Lima.  The study identifies and describes his functions in a catholic school related to planning, organization, management and control based on a review of administrative instruments and interviews carried out.  On the other hand, using the leadership styles from the educational management such as: transformational, pedagogical, distributed, participatory, managerial, transactional, the leadership style of the pastoral principal intended to be described from the perceptions of the members of the educational community.